THE FUNCTION OF MEMORY AND HISTORY IN POSTCOLONIAL LITERATURE - Ibrokhimova, Dilrabo; Komiljonova, Mavluda (GOLDEN BRAIN, 2024)
Postcolonial literature often grapples with the complex interplay between memory and history, presenting them as central themes in articulating the experiences of colonization and its aftermath. Memory serves as a personal and collective tool for reclaiming identity, while history is reexamined to challenge dominant colonial narratives. This article explores how postcolonial writers use memory and history to resist cultural erasure, reconstruct silenced voices, and negotiate identity in postcolonial societies. Through examples from key texts, it highlights how these concepts serve as mechanisms for healing, resistance, and empowerment.